Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
(1,2)
Step-by-step explanation:
Substitution:
x + 2y = 5 Solve for x
x = -2y + 5 Substitute -2y + 5 in for x in the second equation
4x - 12y = -20
4(-2y + 5) - 12y = -20 Distribute the 4
-8y + 20 - 12 y = -20 Combine the y term
-20y + 20 = -20 Subtract 20 from both sides
-20y = -40 Divide both sides by -20
y = 2
Plug y into either of the 2 original equations to get x.
x + 2y = 5
x + 2(2) = 5
x + 4 = 5
x = 1
The answer is (2,1).
Elimination:
x + 2y = 5 4x - 12y = -20. We want to eliminate with the x or the y. I am going to eliminate the x's that means that I have to multiply the first equation all the way through by -4
(-4)(x + 2y) = (5) (-4) That makes the equivalent expression
-4x - 8y = -20 I will add that to 4x - 12y = -20
4x - 12y = -20
0x -20y = -40
-20y = -40
y = 2. Plug 2 into either the 2 original equation to find x. This time I will select the second original equation to find x.
4x -12y = -20
4x - 12(2) = -20
4x - 24 = -20
4x = 4
x = 1
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.